The Effect of LHRH Antagonist Cetrorelix in Crossover Conditioned Media from Epithelial (BPH-1) and Stromal (WPMY-1) Prostate Cells - Siejka, A.; Schally, A. V.; Barabutis, N. (Hormone and Metabolic Research, 2014)
Stromal cells strictly modulate the differentiation of the normal prostate epithelium. In benign prostatic hyperplasia (BPH) tissue, the ratio of stromal to epithelial cells reaches a 5:1 ratio. In this study, we evaluated the effects of crossover conditioned media (CM) of stromal and epithelial prostate cells before and after treatment with LHRH antagonist Cetrorelix. WPMY-1 human prostate stromal cells and BPH-1 human benign prostatic hyperplasia cells were cultured in vitro and the effects of crossover conditioned media (CM) from those cells were studied. We evaluated the effect of Cetrorelix on the expression of PCNA and p53 in those cells. We then studied the effect of Cetrorelix on BPH-1 cells cultured with the CM from WPMY-1 cells, as well as the mechanisms which govern these interactions. CM from WPMY-1 cells strongly stimulated the proliferation of BPH-1 cells in a dose dependent manner, while CM from BPH-1 cells only slightly increased the proliferation of WPMY-1 cells. Cetrorelix inhibited the proliferation of both cell lines and the expression of PCNA, while the expression of p53 was increased. Cetrorelix also inhibited the proliferation of BPH-1 cells stimulated with the CM from WPMY-1 cells. In the crossover experiment, conditioned media from WPMY-1 and BPH-1 cells increased the expression of phosphorylated ERK1/2 and STAT3. Our results support previous observations on the bidirectional stromal-epithelial interactions in prostate gland and shed more light on the mechanistic action of those effects. Our study strongly supports the hypothesis that LHRH antagonists may be beneficial for BPH prevention and treatment.
Keywords: LHRH receptor; LHRH antagonist; Cetrorelix; benign prostatic hyperplasia; WPMY-1; BPH-1